Anxiety associated with family caregiver role in caring for the dependent person - Silva, Marta (2021)
Background: most home care to dependent person is provided by a caregiver, family member of the person being cared for, who provides care in an unpaid manner. Nowadays, there are growing concerns about his mental health, and anxiety and burden are often associated with the caregiver role. Objective: to analyse the relation between sociodemographic variables and caregiver burden and anxiety. Methodology: quantitative, transversal study, with a snowball sample of 85 caregivers. The Zarit Burden Interview Scale and The Depression Anxiety Stress Scale and t Student, Kruskal-Wallis and U Mann-Whitney tests were used. Results: caregivers had a mean age of 51.97 years, were mostly female, married and had education up to nineth grade. It was found that 38.8% of caregivers had anxiety. Those who showed greater anxiety were between 50 and 60 years old (p=0.023) and had higher education (p=0.009). There are no statistically significant differences between other variables. Conclusion: age and education seem to have an influence on caregiver anxiety. Since the caregiver's anxiety can have repercussions on the person being cared for, it is extremely important to prevent and promote their mental health.